2017
DOI: 10.1002/j.0022-0337.2017.81.2.tb06260.x
|View full text |Cite
|
Sign up to set email alerts
|

Dental Hygiene, Dental, and Medical Students’ OMFS/Hospital Dentistry‐Related Knowledge/Skills, Attitudes, and Behavior: An Exploration

Abstract: Engaging other health care providers in oral health-related activities and interprofessional care (IPC) could increase access to oral health care for underserved populations in the U.S. The aims of this study were to assess dental hygiene, dental, and medical students' intra-and interprofessional and oral and maxillofacial surgery (OMFS)/hospital dentistry-related knowledge/skills, attitudes, and behavior; determine whether first and second year vs. third and fourth year cohorts' responses differed; and explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…18 There is a difference in the relation between oral health and hygiene among students of students of dental medicine and students of other faculties. Munz et all 19 showed that the medical students had lower oral health-related and less positive attitudes about oral healthrelated behavior than the dental hygiene and dental students. According to them, third-and fourth-year dental students' knowledge, skills and behavior were higher than those of firstand second-year students.…”
Section: Resultsmentioning
confidence: 98%
“…18 There is a difference in the relation between oral health and hygiene among students of students of dental medicine and students of other faculties. Munz et all 19 showed that the medical students had lower oral health-related and less positive attitudes about oral healthrelated behavior than the dental hygiene and dental students. According to them, third-and fourth-year dental students' knowledge, skills and behavior were higher than those of firstand second-year students.…”
Section: Resultsmentioning
confidence: 98%
“…The vast increase in interdisciplinary teamwork between medicine and dentistry in a hospital setting results in most Hospital Dentists writing progress and plan notes in the patients’ medical charts from a medical providers standpoint. Inter‐professional communication and growth is important for coordinating patient‐centered health care and improving each provider‘s skillset 8 …”
Section: Discussionmentioning
confidence: 99%
“…It would be useful to compare our results with findings from other health professions concerning the frequencies with which these programs engage in IPE and with which disciplines they collaborate most often. However, while several studies have assessed students’ IPE‐related attitudes in dentistry, 25 29 medicine, 22 , 25 , 30 nursing, 27 , 31 33 and pharmacy, 26 , 29 the results of studies with program directors or deans are much less available. In 2012, Formicola et al published a survey of dental school deans 15 .…”
Section: Discussionmentioning
confidence: 99%